2020
DOI: 10.3390/met10020173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wavy Bending on Microstructure and Mechanical Properties of a Rolled AZ31 Sheet

Abstract: In the present work, cross-wavy bending at room temperature was carried out to tailor the microstructure and stretch formability of rolled AZ31 sheets. Wavy bending processing generates profuse {10–12} twins and a tilt basal texture. Subsequent recrystallization annealing causes grain coarsening and enhances the intensity of twin-orientation. The combined use of wavy bending and annealing can maintain high tensile ductility and remarkably enhances the stretch formability of rolled AZ31 sheet. It can be mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…An analysis of the existing methods and means for determining the degradation of the mechanical properties of materials during the operation of structures in real time showed that they are all intended for the study of one type of deformation: tension [ 37 , 38 , 39 ] or bending [ 40 , 41 , 42 , 43 ], while under real conditions loading forces act on the material, under combined conditions of deformation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Relative Workmentioning
confidence: 99%
“…An analysis of the existing methods and means for determining the degradation of the mechanical properties of materials during the operation of structures in real time showed that they are all intended for the study of one type of deformation: tension [ 37 , 38 , 39 ] or bending [ 40 , 41 , 42 , 43 ], while under real conditions loading forces act on the material, under combined conditions of deformation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Relative Workmentioning
confidence: 99%